Kuhuang alleviates liver fibrosis by modulating gut microbiota-mediated hepatic IFN signaling and bile acid synthesis - Bo Shen; Cui Zhou; Tianyi Gu; Zhenyang Shen; Yuecheng Guo; Weiming Dai; Yang Liu; Jie Zhang; Lungen Lu; Hui Dong (Frontiers Media S.A., 2022)
Background: Liver fibrosis is a common outcome of the pathological progression of chronic liver disease; however, no specific and effective therapeutic agent has been approved for its treatment. We investigated the effects of Kuhuang on liver fibrosis and the underlying mechanisms of action.Materials and methods: To induce hepatic fibrosis, either 3,5-diethoxycarbonyl-1,4-dihydro-collidine (DDC) diet was administered, or bile duct ligation (BDL) surgery was performed on C57BL/6 mice. Kuhuang was orally administered to mice for 7 days before and after bile duct ligation or 4 weeks with a DDC diet. Hematoxylin and eosin, Sirius red staining, and immunohistochemical analyses were performed to evaluate hepatic pathology. Hepatic interferon-β (IFN-β) levels were measured using an enzyme-linked immunosorbent assay. RNA sequencing was performed to examine the gene expression profiles of liver tissues. The mRNA expression of inflammatory, profibrotic, and bile acid (BA)-related genes was further validated by qRT-PCR. A targeted metabolomics assay revealed the alteration of the hepatic bile acid (BA) composition. The composition of the gut microbiota was determined via 16S rRNA sequencing.Results: Treatment with Kuhuang attenuated liver fibrosis and reduced the inflammatory response in bile duct ligation and DDC mouse models. In addition, the hepatic IFN signaling pathway was activated following Kuhuang treatment. Kuhuang treatment also significantly decreased hepatic levels of both primary and secondary BAs. In addition, Kuhuang treatment altered gut microbiota composition, with an increased abundance of interferon-inducing Akkermansia and decreased abundance of bile salt hydrolase-producing Lactobacillus, Clostridium, and Bifidobacterium. Furthermore, the abundance of Akkermansia was positively correlated with the hepatic mRNA expression levels of Ifna4, Ifnb, and Isg15, whereas that of Lactobacillus, Clostridium-sensu-stricto-1, and Bifidobacterium was positively correlated with levels of bile acid synthesis-related genes.Conclusion: Our results suggest that Kuhuang plays a protective role during the progression of liver fibrosis, potentially by altering the composition of the gut microbiota, which consequently activates interferon signaling and inhibits bile acid synthesis in the liver.